Accreditation Assistance Strategies for Muhammadiyah Junior and Senior High Schools in Sukabumi: Strategi Pendampingan Akreditasi Sekolah Muhammadiyah Tingkat SMP dan SMA Sederajat di Sukabumi - juhanda, Aa; Setiono; Noor, Iqbal; Makiyah, Arfatul (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
School accreditation is a vital component in ensuring the quality of education, including in Muhammadiyah schools in Sukabumi. Unfortunately, many of these schools still face serious challenges, such as limited facilities, insufficient human resources, and a lack of understanding of the latest accreditation instruments. To address these challenges, an accreditation mentoring program was implemented using a participatory approach in eight Muhammadiyah schools. The activities included socialization, training, administrative assistance, and accreditation simulations. Evaluation results showed a significant improvement in participants’ understanding, with an average score of 89 categorized as “Good,” along with positive responses regarding the content and facilitators. However, disparities in readiness among schools were still evident, as shown by participants with lower scores. The program also faced technical challenges, particularly in scheduling due to the partners’ busy schedules. The conclusion from this program is that it has proven effective in helping schools prepare accreditation documents, understand the latest instruments, and raise awareness about the importance of a sustainable quality culture. The recommended next steps include increasing the intensity and quality of mentoring, ensuring equal support across schools, and developing internal quality assurance systems so that accreditation becomes part of a continuous improvement effort rather than merely an administrative requirement.